2012
DOI: 10.1016/j.ejso.2012.06.126
|View full text |Cite
|
Sign up to set email alerts
|

393. Hepatic resection for metastatic melanoma in the Netherlands – Survival and prognostic factors

Abstract: Patients with hepatic metastases of melanoma have a very poor prognosis, with a median overall survival of less than 6 months. There are several small heterogeneous studies that have shown an association with prolonged survival in those patients treated with hepatic resection, but the role of surgery remains unclear. We evaluated the safety and efficacy of hepatic resection in a population-based study in the Netherlands for patients with metastatic melanoma and assessed the factors that could affect disease-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…These observations concur with a recent meta‐analysis of 5 studies which reported a significant improvement in overall survival following surgery versus nonoperative management in patients with ocular or cutaneous metastatic melanoma (hazard ratio [HR] = 0.32, 95% confidence interval [CI] = 0.22‐0.46; P < .001) . Prolonged overall survival times were also reported in several noncomparative studies of hepatic resection in patients with ocular or cutaneous melanoma (range, 19‐39 months) (Table ) . Five‐year overall survival rates ranged from 0% to 42% following hepatic resection, although most studies reported rates in excess of 20% (Table ) …”
Section: Surgerysupporting
confidence: 84%
See 4 more Smart Citations
“…These observations concur with a recent meta‐analysis of 5 studies which reported a significant improvement in overall survival following surgery versus nonoperative management in patients with ocular or cutaneous metastatic melanoma (hazard ratio [HR] = 0.32, 95% confidence interval [CI] = 0.22‐0.46; P < .001) . Prolonged overall survival times were also reported in several noncomparative studies of hepatic resection in patients with ocular or cutaneous melanoma (range, 19‐39 months) (Table ) . Five‐year overall survival rates ranged from 0% to 42% following hepatic resection, although most studies reported rates in excess of 20% (Table ) …”
Section: Surgerysupporting
confidence: 84%
“…In 2 large patient series, 60‐day mortality rates were 1.9% and 2.3% . Postoperative complication rates of 15% to 20% were documented in other studies …”
Section: Surgerymentioning
confidence: 66%
See 3 more Smart Citations